Uncovering the influence of sleep in recovery, training and team-sport competition - Pitchford, N. W. (2019)
There is an emerging consensus that sleep is an important part of the post-exercise recovery process for athletes. Evidence suggests that a lack of sleep, or sleep of poor quality, can negatively influence markers of physical, physiological, and perceptual recovery that may impact the subsequent training and performance outcomes of athletes. Moreover, recent findings suggest that increasing total sleep time can improve performance, yet comprehensive evidence is lacking. This has seen an increased focus on the investigation of the sleep behaviours of athlete populations; however, this research often does not consider many important contextual factors, such as the physical sleep environment, competition factors including location, travel and timing, and training-related factors like periodisation and training load exposure. Furthermore, little is known about the physical and physiological influences of sleep on the post-exercise recovery process, and information regarding the amount of sleep that is required to maximise recovery and athletic performance is lacking. The aim of the first study in this thesis was to investigate the influence of physical sleep environment during a pre-season training camp on the sleep behaviours of professional Australian Rules footballers. The results of Study 1 (Chapter 4) describe the sleep behaviours of professional Australian Rules footballers between the home environment and a pre-season camp environment, both during the pre-season training period. Australian Rules footballers went to bed and woke earlier when on camp, spending longer in bed without a significant increase in sleep duration, caused by significantly increased wake after sleep onset. Relative changes to time in bed and wake after sleep onset on camp had a strong negative correlation with absolute home values, suggesting those who spend longer time in bed at home are more likely to experience reduced time in bed in the camp environment. Although there was no significant change in total session rating of perceived exertion (s-RPE) training load, when accounting for daily variations of within-player s-RPE load, both increased and decreased s-RPE load had weak correlations with changes in total sleep time in the home environment. Comparatively, in the camp environment, decreases in s-RPE load displayed a moderate positive relationship with total sleep time, whereas increases in s-RPE load displayed moderate negative correlation with total sleep time. However, daily ambient temperature was ~5°C hotter during the camp environment, compared to the normal home environment, which may have influenced results. A change in physical sleep environment, without external influences such as circadian phase-shifting, altered training schedules or increased total training load reduces the quality of sleep and effects the attainment of increased duration of sleep, despite spending longer periods of time in bed. Furthermore, the individual variation in response to a change in environment stresses the importance of assessing sleep on a case-by-case basis, especially if assessment leads to the provision of interventions designed at improving the sleep of athletes during time spent in unfamiliar physical sleeping environments. The aim of the second study in this thesis was to investigate the role that individual contextual factors (age and chronotype) and environmental factors (competitive matches, competition level, and competition location) have on the sleep behaviours across the pre-season and in-season periods in professional Australian Rules footballers. Study 2 (Chapter 5) found that the individual-specific factor chronotype influences the sleep behaviours of Australian Rules footballers. Furthermore, players went to bed and woke later, resulting in increased time in bed and total sleep time, during the in-season compared to the pre-season. On the night before a match, and the two nights following a match, players spent longer in bed and obtained more sleep compared to the pre-season. In contrast, on match nights players spent less time in bed and obtained less sleep, compared to the night before and the two nights following a match; but obtained similar sleep durations on match nights to during the pre-season. No differences in sleep behaviours were observed between matches played at home or away; however, time in bed and sleep duration were reduced following National-level competition, compared to State-level competition. Collectively, these results suggest that individual chronotype needs to be considered in the evaluation of athlete sleep behaviours, and that sleep behaviours vary between season phases, nights surrounding competition, and between competitive levels. The aim of the third study in this thesis was to determine the influence of changes in load variables during both the pre-season and in-season across 1-, 7-, 14-, 21- and 28-day periods and their relationships with objectively measured sleep behaviours in Australian Rules footballers. Study 3 (Chapter 6) found that same-day increases in volume (total distance and s-RPE) and intensity (relative total distance, high-speed running and very high-speed running) have negative associations with sleep behaviours during both the pre-season and in-season. Cumulative 7-day loads during the pre-season have minimal associations with sleep behaviours, whereas sleep duration was negatively associated with higher 7-day cumulative loads during the in-season period. Increased load measures detrimentally influence sleep behaviours over 14-day, 21-day and 28-day cumulative periods during the in-season. These results suggest that heightened short- and long-term exposure to increased loads have a negative effect on the sleep behaviours of Australian Rules footballers. Therefore, consideration of both the acute and cumulative demands of training and competition should be made in the context of monitoring of Australian Rules footballers sleep. The aim of the fourth study in this thesis was to determine the effect of a single night of sleep extension on physiological, physical, and perceptual recovery. Study 4 (Chapter 7) found that whilst the novel high-intensity intermittent exercise session induced similar post-exercise responses to that of team-sport competition, a single night of increased sleep duration (sleep extension) did not influence markers of neuromuscular, autonomic, perceptual, and hormonal function and status on the morning following a session of high-intensity interval exercise under laboratory-controlled conditions. Longer periods of sleep-intervention may be required to have a beneficial effect on markers of recovery and function following exercise. Finally, the aim of the fifth study in this thesis was to determine the effects of multiple days of post-exercise sleep extension (where a total of 10 h per day for 3 days was obtained) on the status of physiological, physical, and perceptual recovery and physical performance. Study 5 (Chapter 8) found that 2-hour afternoon naps (following 8 h of sleep each night) improves the recovery rate of neuromuscular function. Furthermore, both overnight sleep extension (10 h) and afternoon naps improved the recovery of sprint performance following a session of high-intensity interval eercise that was followed by a night comprised of a 6-hour sleep. Overnight sleep extension appears to enhance recovery of perceptual wellbeing measures after, compared to afternoon naps. These results suggest that both overnight extension and afternoon naps have a postive influence on post-exercise recovery. However, caution should be exercised, as afternoon naps may increase sleep onset latency and wake after sleep onset, and reduce sleep efficiency of subsequent night sleep when performed on consecutive days.